THE INFLUENCE OF ONLINE CUSTOMER REVIEW AND SOCIAL MEDIA INFLUENCER ON PURCHASE DECISIONS HMNS LOCAL PERFUME FOR GENERATION Z TIKTOK USERS IN SURABAYA - Kharisma Eka Ardiansyah; Sugeng Purwanto; Raden Johnny Hadi Raharjo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research investigates how Online Customer Reviews and Social Media Influencers influence the purchase decisions of Generation Z TikTok users in Surabaya regarding HMNS local perfume. Employing a quantitative method, data was gathered through online questionnaires distributed to 96 participants chosen using a purposive sampling technique. Data analysis was conducted using the Partial Least Square (PLS) method. The findings reveal that: (1) Online Customer Reviews significantly and positively impact the purchase decisions of Generation Z users; and (2) Social Media Influencers also exert a significant and positive influence on their decisions to buy HMNS local perfume in Surabaya.